Arabic Teacher’s Humanistic Deauthorization: Online Teaching Experience in Islamic Higher Education - Penny Respati Yurisa; Muassomah, Muassomah; Khoirurrijal, Khoirurrijal; Faisal Mahmoud Adam Ibrahim (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
The distance learning policy poses several challenges for Arabic teachers, students, and parents and causes a decrease in humanistic authority among teachers. Online learning tends to weaken their role in this aspect. This study identifies activities teachers can no longer do during online Arabic learning. In addition, this study also explores the factors that cause the erosion of this humanistic role. Using a qualitative descriptive method through interviews and focus group discussions (FGDs) with several teachers, this study found seven challenging activities for teachers, such as providing individual guidance to students face-to-face. Technology that acts as a communication medium between teachers and students causes limitations in understanding each student's character in depth. It is recommended that educators adopt a more adaptive approach, which can view students as active subjects in the learning process.